Chromosomal aberrations and mutational analysis of BMP-15 gene in amenorrhea - DR.V.RAJITHA,; MRS.G.PANNEER SELVI,; DR. K.C.SHANTHI, (International Journal of Pharma and Bio Sciences, 2018)
Prevalence of amenorrhea is higher in Indian population with a potential social impact. The study of cytogenetic pattern and mutational studies in its correlation with other physiological factors will help for better understanding the cause and earlier diagnosis. BMP15 gene (Bone Morphogenetic Protein 15) Cytogenetic Location: Xp11.2. To find out the cytogenetic pattern and BMP-15 gene mutations among amenorrhea patients and to correlate with the phenotype and clinical findings among these cases. This study was performed on 200 women volunteers after taking an informed consent. Out of 200 cases 100 cases were grouped as controls and 100 cases as study group. Cytogenetic study was done by conventional karyotyping and other clinical investigations (hormonal assay, fasting blood glucose) were also carried out. Mutational analysis was performed on 197 women volunteers. Out of 197 cases 97 cases were grouped as controls and 100 cases as study group using PCR. In the present study the frequency of classic Turner’s (25%) and mosaic Turner’s (12.5%) among primary amenorrhea cases were analyzed. All Secondary amenorrhea cases were with normal chromosomal complement that is 0% frequency of chromosomal aberrations. One case with polycystic ovarian disease exhibited Premature Chromatid Separation (PCS). Mutational analysis showed 46% of the subjects among study group with mutated BMP-15 gene. Identification of known genetic causes could aid in development of effective treatments for women with amenorrhea, as well as earlier diagnosis which may allow for family planning before the onset of amenorrhea.